Genomic profiling reveals subsets of dedifferentiated liposarcoma to follow separate molecular pathways - Rieker, Ralf Joachim; Weitz, Jürgen; Lehner, Burkhard; Egerer, Gerlinde; Mueller, Andrea; Kasper, Bernd; Schirmacher, Peter; Joos, Stefan; Mechtersheimer, Gunhild (Virchows Archiv, 2010)
With the aim to provide more insight into their biology, a series of 79 liposarcomas (LS) representative of all main subtypes was analysed for chromosomal imbalances using comparative genomic hybridization. Based on the genetic data, unsupervised hierarchical clustering unveiled two main LS clusters, each with two subclusters, one comprising three subsets. The first main cluster consisted of one larger subcluster, being characterised by gains/high-level amplifications of chromosomal subregions 12q13-q15, and exclusively included well-differentiated and dedifferentiated LS. A smaller subcluster was set apart on the basis of recurrent gains of 20q13 and 8q24, and mainly comprised pleomorphic and myxoid/round cell LS. The larger subcluster was subdivided into three subsets, one with nearly exclusive overrepresentations of 12q13-q15, the second with additional frequent gains of 1q21-q24, and the third with further recurrent overrepresentations of 6q22-q24, 20q13, and 12q24 and frequent losses of 13q14-q21 and 11q22-q23. While the first subset comprised both well-differentiated and dedifferentiated LS, the second and third subsets entirely included dedifferentiated LS. The second main cluster was characterised by recurrent overrepresentations of 5p13-p15, 1q21-q24, 1p12-p21, and 17p11.2-p12 and essentially comprised pleomorphic and myxoid/round cell LS. A separation of this second main cluster into two subclusters was based on additional gains on 22q13 and losses on 1q42-q43. Genomic profiling reveals genetically distinct subsets of dedifferentiated LS, which are clearly different from pleomorphic, myxoid/round cell, and, for some subsets, from well-differentiated LS. These data indicate that dedifferentiated LS follow separate tumourigenic pathways and that genetic analysis is important to unravel these differences.